Subtle gait and balance impairments occur in idiopathic rapid eye movement sleep behavior disorder. Issue 9 (26th June 2019) - Ehgoetz Martens, Kaylena A.; Matar, Elie; Hall, Julie M.; Phillips, Joseph; Szeto, Jennifer Y. Y.; Gouelle, Arnaud; Grunstein, Ronald R.; Halliday, Glenda M.; Lewis, Simon J. G.
Abstract: Background: Although motor abnormalities have been flagged as potentially the most sensitive and specific clinical features for predicting the future progression to Parkinson's disease, little work has been done to characterize gait and balance impairments in idiopathic rapid eye movement sleep behavior disorder (iRBD). Objective: The objective of this study was to quantitatively determine any static balance as well as gait impairments across the 5 independent domains of gait in polysomnography‐confirmed iRBD patients using normal, fast‐paced, and dual‐task walking conditions. Methods: A total of 38 participants (24 iRBD, 14 healthy controls) completed the following 5 different walking trials across a pressure sensor carpet: (1) normal pace, (2) fast pace, (3) while counting backward from 100 by 1s, (4) while naming as many animals as possible, (5) while subtracting 7s from 100. Results: Although no gait differences were found between the groups during normal walking, there were significant differences between groups under the fast‐paced and dual‐task gait conditions. Specifically, in response to the dual tasking, healthy controls widened their step width without changing step width variability, whereas iRBD patients did not widen their step width but, rather, significantly increased their step width variability. Similarly, changes between the groups were observed during fast‐paced walking wherein the iRBD patients demonstrated greater step length asymmetry when compared with controls. Conclusions: This study demonstrates that iRBD patients have subtle gait impairments, which likely reflect early progressive degeneration in brainstem regions that regulate both REM sleep and gait coordination. Such gait assessments may be useful as a diagnostic preclinical screening tool for future fulminant gait abnormalities for trials of disease‐preventive agents. © 2019 International Parkinson and Movement Disorder Society